International Student Transitions: A Framework for Success - Uddin, Muhammad Sharif (Journal of International Students, 2021)
Andrade and James Hartshorn (2019) surrounds the transition that international students encounter when they attend universities in developed countries in pursuit of higher education. Andrade and James Hartshorn (2019) describe how some countries like Australia and the United Kingdom host more international students than the United States (U.S.) and provides some guidelines for the U.S. higher education institutions to follow to host more international students. This book contains seven chapters.